Petrographical and geochemical evidences for paragenetic sequence interpretation of diagenesis in mixed siliciclastic–carbonate sediments: Mozduran Formation (Upper Jurassic), south of Agh-Darband, NE Iran - Mahboubi, A.; Moussavi-Harami, R.; Carpenter, S.; Aghaei, A.; Collins, Lindsay (Springer, 2010)
The Upper Jurassic Mozduran Formation with a thickness of 420 m at the type locality is the most important gas-bearing reservoir in NE Iran. It is mainly composed of limestone, dolostone with shale and gypsum interbeds that grade into coarser siliciclastics in the easternmost part of the basin. Eight stratigraphic sections were studied in detail in south of the Agh-Darband area. These analyses suggest that four carbonate facies associations and three siliciclastic lithofacies were deposited in shallow marine to shoreline environments, respectively. Cementation, compaction, dissolution, micritization, neomorphism, hematitization, dolomitization and fracturing are diagenetic processes that affected these sediments.Stable isotope variations of δ18O and δ13C in carbonate rocks show two different trends. High depletion of δ18O and low variation of δ13C probably reflect increasing temperatures during burial diagenesis, while the higher depletion in carbon isotope values with low variations in oxygen isotopes are related to fresh water flushing during meteoric diagenesis. Negative values of carbon isotopes may have also resulted from organic matter alteration during penetration of meteoric water. Fe and Mn enrichment with depletion of δ18O also supports the contention that alteration associated with higher depletion in carbon isotope values with low variations in oxygen isotopes took place during meteoric diagenesis. The presence of bright luminescence indicates redox conditions during precipitation of calcite cement.